Iranian Female Adolescent's Views on Unhealthy Snacks Consumption: A Qualitative Study - R Majdzadeh; A Rashidian; M Bazargan; N Omidvar; A Karimi-Shahanjarini; D Shojaeizadeh (Tehran University of Medical Sciences, 2010)
"nBackground: Given the increasing prevalence of obesity among Iranian adolescents and the role of consumption of unhealthy snacks in this issue, interventions that focus on factors influencing food choice are needed.  This study was designed to delineate factors associated with unhealthy snack use among female Iranian adolescents."nMethods: The theory of Planned Behavior served as the framework of the study.  Qualitative data were collected via nine focus group discussions in two middle schools (6th to 8th grades) in a socio-economically diverse district in the city of Tehran in spring 2008. The study sample included 90 female adolescents aged 12-15 years. The sampling strategy was purposive method. Data analyzed using the "framework" method."nResults: Major factors identified by the respondents were taste, peer pressure, parental influence, easy access to unhealthy snacks, limited availability of healthy snacks, appeal of snacks, habit, high price of healthy snacks, and media advertisements. Nutritional value and healthiness was not one of the first priorities when buying snacks, as adolescents thought it was too early for them to worry about illness and adverse consequences of eating junk foods."nConclusions: For developing culturally sensitive evidence-based interventions that can motivate adolescents to choose healthy snacks, a broad range of factors should be taken into account.